Pentingnya Pendidikan Finansial dalam Meningkatkan Kemampuan Manajemen Uang pada Anak-Anak - Intan Shakira, Natasya; Amrona Rosyada, Yassirly; Fadlilah, Siti Alfiyani; Aini, Nurul; Rahma Permana, Ardiyan (Indra Institute Research & Publication, 2024)
Financial education should start at an early age. Financial management aims to form good money management habits, minimize the risk of wasteful behavior, and prepare young people to make more mature financial decisions in adulthood. Unfortunately, most parents do not direct their children how to manage the pocket money given so that children tend to behave consumptive. In line with the research of Jorgensen & Savla (2019) which emphasizes the importance of the role of parents in providing financial education, combined with formal education at school. This study aims to determine the importance of financial education in improving children's money management skills with an educational approach in the form of learning through UIN Salatiga's community service program. The method used in this research is direct observation in North Kiringan Hamlet. The results showed that the lack of financial education in children can lead to poor financial management, low financial independence, and vulnerability to fraud. The implication of this research can prevent poor financial management, trigger an attitude of financial independence, reduce opportunities for financial investment fraud.